2019
DOI: 10.1186/s12882-019-1412-0
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of kidney transplantation from elderly donors after circulatory death (GEODAS study)

Abstract: Background Spain has dramatically increased the number of controlled circulatory death donors (cDCD). The initial selection criteria for considering cDCD for kidney transplantation (KT) have been expanded progressively, with practically no limits in donor age during the last years. We aimed to analyze the early clinical outcomes using expanded (> 65 years) cDCD in comparison with standard ones. Methods Observational multicenter study including 19 transplant centers in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…The first experiences were not very positive and described no benefit in terms of survival using kidneys from old DCDs (>65 years) compared with those who remained waitlisted on dialysis [ 15 , 16 ]. Since then, other studies have supported good death-censored graft survival and acceptable graft function in >65-year cDCD grafts, comparable to results from elderly DBDs [ 18 , 35 ]. Khalid et al [ 35 ] showed an overall death-censored graft survival of 90 and 80% at 3 and 5 y, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The first experiences were not very positive and described no benefit in terms of survival using kidneys from old DCDs (>65 years) compared with those who remained waitlisted on dialysis [ 15 , 16 ]. Since then, other studies have supported good death-censored graft survival and acceptable graft function in >65-year cDCD grafts, comparable to results from elderly DBDs [ 18 , 35 ]. Khalid et al [ 35 ] showed an overall death-censored graft survival of 90 and 80% at 3 and 5 y, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…The increase in the availability of cDCD organs is mainly due to the use of older donors [ 9 , 18 , 25 ], which may result either from a better evaluation of potential donors in this age group or a greater utilization of these grafts. In fact, elderly donors constitute nearly 25% of cDCDs in Spain [ 18 , 26 ] and represented up to 52.9% of all cDCD-KTs in our cohort. So far, age-matching allocation policies have shown favourable results [ 10–13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations